The importance of compression sonoelastography in improving the diagnostics of the pathology of myometrium - Sharmazanova, Olena; Safonova, Inessa; Mityakova, Yulia (Scientific Route OÜ, Estonia, 2021)
The diversity of the clinical picture and the asymptomatic nature of the clinical manifestations of myometrial pathology cause difficulties in diagnosis. There is a lack of reliable diagnostic criteria for this pathology, in particular, imaging, especially with the simultaneous combination of adenomyosis and leiomyoma. The aim of the research. Determination of the possibility of compression sonoelastography in the diagnosis of myometrial pathology and determination of its sonoelastography characteristics in leiomyoma and adenomyosis, as well as comparison of sonoelastography results with histological data. Materials and methods. Elastography images of 155 patients with adenomyosis and leiomyoma, as well as combined pathology, were analyzed, the elastography diagnosis of which was confirmed by histological examination. Results. Leiomyoma and adenomyosis had different elastography characteristics (strain ratios) with different color mapping; their specific characteristics and main differences are determined. Based on sonoelastography, the majority of patients (n = 30) were suspected of having uterine fibroids, 14 had adenomyosis, and 42 had adenomyosis and fibroids. Sonoelastography revealed histological signs of adenomyosis in 3 patients with uterine leiomyoma. Conclusions. Ultrasound examination using compression sonoelastography in such pathological conditions of the myometrium as adenomyosis and leiomyoma, as well as unchanged myometrium, makes it possible to determine changes in the degree of elasticity of the myometrium in the corresponding pathology. Sonoelastography allows the identification of clear distinguishing features of fibroids and adenomyosis. The unchanged myometrium has a certain elasticity, which can be equated to a specific numerical value – the coefficient of deformation. This indicator has different meanings in myoma and adenomyosis, which makes it possible to differentiate these pathological conditions of the myometrium. Compression sonoelastography is able to identify clear distinguishing features of leiomyoma and adenomyosis, and consistency of diagnoses based on sonoelastography and histology is significant but not optimal.
Keywords: adenomyosis; leiomyoma; compression sonoelastography; uterus; myometrium; ultrasound; study; image; deformation ratio